(untitled) (Journal of Information Systems and Technology Management, 2009)
This research studies the influence range of the organizational, planning and technical factors within the information quality, system quality and information systems services quality, in the user satisfaction, based on the designed model research for this purpose. The empirical study takes place in six Higher Education Institutes (94 questionnaires) by the Partial Least Square statistic tool. The results has shown that Organizational Factor (information needs, management support, institutional objectives satisfaction) is which has the most impact because its high correlation value (R=0.624; R=0.435 yR=0.428) and signifi cance (p